Application of Shear-Wave Elastography in the Evaluation of Hamstring Stiffness in Young Basketball Athletes - Paige Cummings; Nathan D. Schilaty; Takashi Nagai; Luca Rigamonti; Ryo Ueno; Nathaniel A. Bates (International Journal of Sports Physical Therapy)
# Background